Optoelectronics / Emmanuel Rosencher and Borge Vinter ; translated by P.G.Piva. - Rosencher, Emmanuel, 1952- (Cambridge University Press, 2002)
Optoelectronics is a practical and self-contained graduate-level textbook on the subject. Concepts explored include quantum mechanics of electron-photon interaction, quantisation of the electro-magnetic field, and semiconductor properties.